Wat op dees (van) aarde beteken die einde van tradisionele metafisiese taal oor God? In gesprek met die Nuwe-Testamentikus Andries Gideon van Aarde oor sy verstaan van "n postsekulêre spiritualiteit - Veldsman, Daniël P. (HTS teologiese studies, 2011)
What does the end of traditional metaphysical language about God mean? In conversation with New Testament scholar Andries Gideon van Aarde on his understanding of a postsecular spiritualitySouth African New Testament scholar Van Aarde’s explorative search for a new direction in theological reflection is explicated in this article with reference to his discussion of Peter Berger and Charles Taylor’s contemporary contributions, which Van Aarde takes as vantage point to articulate the meaning of his ‘courage to be a religious person today’. The articulation of his ‘courage’ to pursue a post-theistic understanding of a contemporary Christian religiosity (read: spirituality) that is non-fundamentalistic, non-populist and post-secular is discussed. At the same time, the basic tenets of his explorations are indicated, being constituted – negatively – by a de-centering of the power of institutional religion and, positively, by the enchantment of a Biblical hermeneutics that does not emphasise a proposition-like and moral code-like reading strategy. Finally, his ‘new direction’, which finds expression in the articulation of a ‘spirituality of living faith’, is scrutinised. It exposes the shortcomings in his (individualistic) exposition within the new correlation of modernisation and pluralism, causing it subsequently to bypass the necessary contemporary outcome in social embodiment.